Pengaruh Kualitas Air Hasil Pengolahan Limbah pada Kolam Fakultatif Terhadap Daya Tetas Telur Ikan Nila (Oreochromis niloticus) - Rizki Qorin Nabila; Hamdani Dwi Prasetyo; Husain Latuconsina (Jurnal Riset Perikanan dan Kelautan, 2023)
Nile Tilapia (Oreochromis niloticus) is one of the economically important fish to be cultivated. Although tilapia is able to adapt to changes in environmental conditions, tilapia is a fish that is sensitive to pollutant exposure. Exposure to various types of pollutants has been reported to have caused death and physiological disturbances in tilapia. This study aims to analyze the effect of several water quality parameters (temperature, pH, DO, and turbidity) fed facultative pond waste water with different processing stages on the hatchability of tilapia (Oreochromis niloticus) eggs. The method used was the experimental method using RAL (completely randomized design) with 4 treatments. Each treatment consisted of 3 replications with treatment A (facultative pond water 1 with high turbidity level), treatment B (1 liter facultative pond water 4). with medium turbidity level), C treatment (1L of facultative 6 pool water with low turbidity level) and D treatment (1L of water from Ngsong Village). Data were analyzed using simple linear regression to determine the effect of water quality on hatchability of tilapia eggs and their correlation. The results of water quality obtained during observations on temperature parameters ranged from 21-27ÂºC with a pH ranging from 4.91-7.91, DO ranging from 3.52-5.65 and turbidity ranging from 1.9-0.5. Water quality parameters including temperature, pH, dissolved oxygen have different effects on the hatchability of tilapia (Orecohromis niloticus) eggs. Temperature has a significant influence on egg hatchability of 53% with a strong positive relationship. pH and DO have a small weak effect on the hatchability of tilapia (Oreochromis niloticus) eggs of 0.15 and 0.25 respectively with a weak positive relationship. Meanwhile, turbidity has a large effect, namely 73% on egg hatching, with a strong negative relationship. This means that increasing temperature, pH and dissolved oxygen tend to increase egg hatchability, while increasing turbidity will reduce the hatchability of tilapia (Oreochromis niloticus) eggs.